Ewolucja struktury rządu w wysoko rozwiniętych państwach burżuazyjno-demokratycznych: [Evolution of the structure of government in highly developed burgeois-democratic countries] (Studia Prawnicze / The Legal Studies, 1981)
The Author begins with presentation of his opinion on transformations of structure of government. To a preponderant degree these changes are conditioned by widening of functions of a state, by changes in the character of such functions and techniques of their realization. This means that among other factors con- ditioning evolution there are factors linked with class character of a state and those of inter-formational character, equally important.Next, in a synthetic survey, the Author expresses his view according to which widening of such tasks causes the increase of importance of efficiency of a state in the process of their realization. This does not mean, however, that solutions of managerial and technocratic character are excluded, since techniques of management should be submitted’ to political and social choices and to the hierarchy of needs and values which are established in result of confrontation of various platforms of social and administrative experience.Finally, speaking of the process of evolution of the structure of government, the Author comes to the issues such as: experience showing the importance of limiting the number of members of the government; transformations of departamental structure; extent and forms of employing “younger ministers”; institutionalization of governmental management by the prime minister or president the extent to which governmental commissions are utilized.Limiting his remarks to the above issues, the Author points out to the fact that issues of evolution of departmental management require separate presentation.